Impact of biochar and compost amendment on corn yield and greenhouse gas emissions under waterlogged conditions - Han-Na Cho; Minji Shin; Ikhyeong Lee; Haeun Ryoo; Bharat Sharma Acharya; Jae-Hyuk Park; Yong Hwa Cheong; Ju-Sik Cho; Se-Won Kang (Applied Biological Chemistry, 2023)
Abstract Biochar, widely recognized for its capacity to counteract climate change impacts, has demonstrated substantial benefits in agricultural ecosystems. Nevertheless, empirical studies exploring its efficacy during climatic aberrations such as heavy rainfall are limited. This study investigated the effects of compost and biochar addition on corn growth attributes, yield, and soil CO2 and N2O fluxes under heavy rain (exceeding 5-yr average) and waterlogging conditions. Here, treatments included compost (CP, 7.6 t ha−1); rice husk biochar (RB, 7.6 t ha−1); wood biochar (WB, 7.6 t ha−1); and control (Cn). Under high rainfall and waterlogging, the CP treatment manifested a pronounced enhancement in corn biomass and productivity, exceeding biomass and productivity of Cn treatment by 12.6 and 32.2%, RB treatment by 120 and 195%, and WB treatment by 86.1 and 111%, respectively. Corn yield increased in the order: CP > Cn > WB > RB. Intriguingly, negligible disparity occurred between the RB and WB treatments in straw yield, grain yield, grain index, and corn productivity but both treatments recorded distinctively lower values than CP treatment. Also, the CO2 and N2O fluxes remained largely similar for two biochar treatments but lower than CP treatment. Overall, CP increased corn yield, straw, and grain yield whereas biochars reduced N2O flux during waterlogging. Although derived from a short-term experimental window, these pivotal findings furnish invaluable insights for devising soil amendments for yield and environmental benefits in contexts of extreme climatic perturbations. Our findings offer a robust foundation for refining nutrient management strategies confronted with waterlogging challenges, but long-term studies are necessary for definitive conclusions.